EFFECT OF BENTONITE AS FILLER IN COMPOSITE MEMBRANE PERFORMANCE POLYVINYLIDENE FLUORIDE (PVDF)-POLYMETHYLMETHACRYLATE (PMMA) - Erda Marniza; Marlina .; M Nasir (Jurnal Natural, 2018)
Abstract. The effect of bentonite as filler on the performance of the composite membrane of PVDF-PMMA has been performed. This study was conducted to determine the performance PVDF-PMMA composite membranes and membrane applications PVDF-PMMA-Bentonite on oily wastes. Bentonite is obtained from North Aceh while PVDF membrane-PMMA by phase inversion method. This study uses an oily waste water model was made by mixing surfactant tween 80 with concentration of 2% with palm oil and gas oil. Membrane PVDF-PMMA-Bentonite is analyzing using cell ultrafiltration (flux test), FTIR and SEM-EDX. The results showed that the value of flux with the addition of bentonite is greater than without bentonite. Good flux values contained in the PVDF-PMMA-Bentonite (1:1:2) amounted to 32.143 L/m2.h.bar with permeability of 21.428 L/m2.h. FTIR characterization analysis results show that bentonite can add to pore at wave number 1520 cm -1 and 1660 cm-1 SEM and EDX results showed regular shape and uniform pore. Keywords: Membrane, bentonite, filler, FTIR, SEM-EDX, Oily wastewater